Computer Network Design in Vocational School Using Network Simulator - Kamu, Israel; Parinsi, Mario Tulenan; Kuhu, Meikel Wolter; Mananggel, Arther Valentino (JR Education, 2022)
The development of computer network technology is currently increasing rapidly along with the community's need for services that utilize computer networks. A computer network is a relationship between 2 or more computers connected by wired or wireless transmission media. This study aims to As for the purpose of this research is to analyze and design a computer network at SMK Negeri 1 Tabuk Utara. The research model uses the Network Development Life Cycle (NDLC) with six stages, namely analysis, design, simulation prototype, implementation, monitoring and management. However, only the first to third stages were carried out. After being developed through several stages, the results of this study show that by analyzing and designing network designs using Cisco packet tracer, SMK Negeri 1 Tabuk Utara already has 2 design models to be used directly in this design accompanied by material estimation and work on the computer network.